Development of Gusjigang-Based Parenting Model for Early Childhood - Aliyah, Risyda; Suad; Gudnanto (ICCCM Journal of Social Sciences and Humanities, 2024)
Early childhood education plays a very important role and determines the history of subsequent child development because it is the foundation for the child’s personality. The learning process must refer to the characteristics of early childhood development and all the natural characteristics inherent in children. Likewise, the stimulus provided needs to be adapted to the characteristics and nature of these early childhood. This study aims to describe the effectiveness of the Gusjigang-based parenting model development module in parental collaborative education in early childhood. The research method used is quantitative with a one-group pretest-posttest design approach. The subjects in this study were three educators and six parents in Pertiwi Kindergarten, Cahaya Kindergarten and Masjid Agung Kudus Kindergarten, respectively. Data collection techniques using test instruments. The instruments were arranged according to the core competencies of early childhood education and the philosophy of Gusjigang. The researcher conducted the research using pretest and posttest questions. The t-test results show that Ha is accepted and Ho is rejected, meaning there are differences in learning outcomes before and after learning through outreach to educators and parents. Based on the results of this study, the Gusjigang-based parenting development model in collaborative education of parents in early childhood in Kindergarten, Demaan Village, Kudus City District, is feasible and effective.